Get expert insights and community-driven knowledge on IDNLearn.com. Discover trustworthy solutions to your questions quickly and accurately with help from our dedicated community of experts.
Sagot :
To solve the problem of finding suitable functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that [tex]\( h(x) = (f \circ g)(x) = 5(x+1)^3 \)[/tex], let's break it down step-by-step.
Given:
[tex]\[ h(x) = 5(x + 1)^3 \][/tex]
We need to find functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that:
[tex]\[ h(x) = f(g(x)) \][/tex]
Let's examine the options provided:
### Option A:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = (x + 1)^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f((x + 1)^3) = 5((x + 1)^3)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^9 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option B:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x + 1) = 5(x + 1)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^3 \][/tex]
This matches [tex]\( h(x) \)[/tex].
### Option C:
[tex]\[ f(x) = (x + 1)^3 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = (5x^3 + 1)^3 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option D:
[tex]\[ f(x) = x + 1 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = 5x^3 + 1 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
Given the solutions above, only Option B is a valid combination of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] that satisfies [tex]\( h(x) = 5(x + 1)^3 \)[/tex].
Therefore, one possibility for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] is:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Given:
[tex]\[ h(x) = 5(x + 1)^3 \][/tex]
We need to find functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] such that:
[tex]\[ h(x) = f(g(x)) \][/tex]
Let's examine the options provided:
### Option A:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = (x + 1)^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f((x + 1)^3) = 5((x + 1)^3)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^9 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option B:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(x + 1) = 5(x + 1)^3 \][/tex]
This simplifies to:
[tex]\[ f(g(x)) = 5(x + 1)^3 \][/tex]
This matches [tex]\( h(x) \)[/tex].
### Option C:
[tex]\[ f(x) = (x + 1)^3 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = (5x^3 + 1)^3 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
### Option D:
[tex]\[ f(x) = x + 1 \][/tex]
[tex]\[ g(x) = 5 x^3 \][/tex]
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f(5 x^3) = 5x^3 + 1 \][/tex]
This does not match [tex]\( h(x) \)[/tex].
Given the solutions above, only Option B is a valid combination of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] that satisfies [tex]\( h(x) = 5(x + 1)^3 \)[/tex].
Therefore, one possibility for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] is:
[tex]\[ f(x) = 5 x^3 \][/tex]
[tex]\[ g(x) = x + 1 \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For trustworthy answers, rely on IDNLearn.com. Thanks for visiting, and we look forward to assisting you again.